Assessing the survival of MRC5 and a549 cell lines upon exposure to pyruvic Acid, sodium citrate and sodium bicarbonate - biomed 2013 - Farah, Ibrahim O; Lewis, Veshell L; Ayensu, Wellington K; Cameron, Joseph A (Biomedical sciences instrumentation, 2013)
Lung cancer is among the most prevalent and deadly cancers in United States. In general, cancer cells are known to exhibit higher rates of glycolysis in comparison to normal cells. In attempting to exploit this unique cancer-dependent ATP generation phenomenon, it was our hypothesis that upon exposure to organic inhibitors of glycolysis, cancer cells would not survive normally and that their growth and viability would be vastly decreased; essential glycolytic ATP production will be exhausted to the point of collapsing energy utilization. Furthermore, we hypothesize that no negative effect would be seen with exposures to organic inhibitors for normal lung cells. The human lung fibroblast MRC-5 and the human A549 alveolar epithelial cell lines were used as in vitro models of normal lung and lung cancers respectively. Using standard methods, both cell lines were maintained and exposed to pyruvic acid, sodium citrate and sodium bicarbonate reagents at concentration levels ranging from 31.3-2,000 µg/ml in 96 well plates in quadruplets and experiments repeated at least three times using MTT, and cell counting (T4 Cellometer) assays as well as phase-contrast photo-imaging for parallel morphological displays of any changes in the course of their vitality and metabolic activities. Our results indicate that exposure of both cell lines to these organics resulted in concentration dependent cell destruction/cell survival depending on the cell line exposed. Pyruvic acid, sodium citrate and sodium bicarbonate showed statistically significant (p<0.05) differential negative effects on the A549 cell line in comparison to its unexposed control as well as to their effects on the MRC-5 cell line, presenting a potential promise for their use as cancer biotherapeutics.